AMFIBIA DAN REPTILIA CAGAR ALAM GUNUNG SUPIORI, BIAK-NUMFOR: DAERAH KORIDO DAN SEKITARNYA - Kurniati, Hellen (Research Center for Biology-Indonesian Institute of Sciences, 2003)
During three weeks field work survey (16th June-7 July 1999) on seven habitat types in Gunung Supiori Nature Reserve, Biak-Numfor District, Papua 21 species of reptiles (six species of geckos, nine species of skinks, one species of monitor lizard and five species of snakes) and two species of amphibians were found.On all of identified species, no one is endemic species in Supiori Island, although the island has drifted for 200 million years ago.The phenomena has been occurring in this area is tend to be Brown Phenomena (Brown, 1997).Based on information from local people, two species of sea turtles (Chelonia mydas and Eretmochelys imbricata) occur barely in surrounding waters and population status of Crocodylus porosus the species that inhabitant in mangrove has already been extinct since 1980-year era.Population status of reptiles that listed in Appendix II CITES, such as Candoia aspera and some species of reptiles and frogs that listed as non-appendix CITES are almost still in good condition; the good population status is also occur on protected monitor lizard Varanus indicus.